Terapi Plasma Exchange Pada Pasien Sindroma Guillain Barre - Lasmaria Flora Roslinda Silaen (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Plasma Exchange Therapeutic that is done to the patient of Guillain Barre Syndrome can eliminate antibody pathogen which is useful for improvement of patient’s condition.